PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS IT DI DESA LUNU KECAMATAN NUNLEU KABUPATEN TIMOR TENGAH SELATAN - Wira Syahputra, Andrian; Leobisa, Jonathan; Adi Saingo, Yakobus (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The learning presented by teachers must be interesting, so that it can arouse students' enthusiasm and interest in learning, therefore teachers need to be equipped to create creative learning activities, including by utilizing IT which is centered on the use of Canva and learning videos via Power Point. Training through PkM activities aims to provide teachers with an understanding of the importance of IT-based learning media, as an effort to improve the process and quality of learning in schools, and how schools cannot avoid facing the era of modernization and the internet. PkM (Community Service) activities are carried out in the form of education and training in making IT-based learning media. The training material delivery method consists of lecture, question and answer, discussion and direct practice in creating IT-based learning media. The training results show that participants' understanding and mastery of the material regarding creating IT-based learning media has increased after attending the training compared to before. Apart from that, training participants already have the skills and ability to create their own learning media, such as making learning videos using Power Point and using the Canva application to create weekly and monthly activity schedules to support the smooth running of various activities at school.